Genetic testing and family entanglements. (April 2022) - Dimond, Rebecca; Doheny, Shane; Ballard, Lisa; Clarke, Angus
Abstract: The development of the 'new genetics' in the early 1990's opened up a new space which required some patients and families to understand and navigate genetic testing. The social science literature that has grown alongside the 'new genetics', now spanning more than thirty years, has continued to explore and question assumptions about attitudes and responses towards genetic technologies. In this article we highlight how individual experience of genetic disease and personal responses towards genetic technologies can only be understood by considering their context. We focus on the rich literature on family within sociology, science and technology studies, anthropology, and family studies, to explore the myriad ways in which family is implicated in the patient experience of genetic testing. We explore these connections by drawing on a set of interviews held with individuals who have undergone a predictive test for a genetic condition, including Huntington's Disease and breast cancer. Five themes were developed: family disclosure, family gatekeeping, going for testing, individual and collective communication practices, and receiving a negative test result. To conclude, we highlight how these connections might be considered through the lens of entanglement, explaining the complex mechanisms through which family and genetics are intimately entwined. Highlights: We explored the early stages of decision making about predictive genetic testing. The concept of entanglement was used to explore the role of family in genetics. The family act as gatekeepers and communicators of genetic information. Barriers to family communication include the desire to protect and respect others. Family entanglements continue to shape communication and experience.